2012
DOI: 10.1177/0013916512458579
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Evidence for Spatial Bias in Beliefs About the Severity of Environmental Problems

Abstract: Prior research has shown a tendency for environmental problems to be rated as more severe at the global level than at the local level. The present article reports reanalyses of a large cross-cultural data set (Study 1: k = 22, N = 3,277) and new cross-cultural data (Study 2: k = 8, N = 1,131) examining the prevalence of this spatial bias in the rated severity of environmental problems Article 268 Environment and Behavior 46(3)along with analyses of individual and country-level predictors of this bias. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 57 publications
4
76
1
7
Order By: Relevance
“…Consistent with the previous literature on flood risk (Baan & Klijn, 2004;Stefanovic, 2003;Terpstra et al, 2006), risk perception has been found to be a predictor of preventive behaviour. However, considering the affective level, it was predicted that place attachment may negatively moderate this positive relation, according to the possible effect of place-specific biases, such as the optimistic bias applied to environmental risk perception (Gifford et al, 2009;Radcliffe & Klein, 2002;Schultz et al, 2014). This restraining effect should be stronger for contexts where the risk is higher and where the bias may be greater.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Consistent with the previous literature on flood risk (Baan & Klijn, 2004;Stefanovic, 2003;Terpstra et al, 2006), risk perception has been found to be a predictor of preventive behaviour. However, considering the affective level, it was predicted that place attachment may negatively moderate this positive relation, according to the possible effect of place-specific biases, such as the optimistic bias applied to environmental risk perception (Gifford et al, 2009;Radcliffe & Klein, 2002;Schultz et al, 2014). This restraining effect should be stronger for contexts where the risk is higher and where the bias may be greater.…”
Section: Discussionmentioning
confidence: 99%
“…Past research has shown that individuals view environmental risks as more likely to happen elsewhere, thus affecting other people and other local areas rather than themselves (e.g., Dunlap et al, 1993;Gifford et al, 2009;Hatfield & Job, 2001;Lima & Castro, 2005;Pahl et al, 2005;Uzzell, 2000). This bias, based on unrealistic optimism, is likely to function as a barrier for individuals to face local environmental problems (Schultz et al, 2014). However, spatial optimism may occur not only by the comparison of local vs. global (Gifford et al, 2009) or here vs. there (Hatfield & Job, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations